Effect of hot etching with HF on the surface topography and bond strength of zirconia - Liang, Zhuoran; Liu, Yang; Jiang, Yulin; Liu, Pan; Zhang, Yannan; Meng, Fanhao; Liu, Min; Cui, Zhi; Ma, Jinbao; Chen, Jianfeng (Frontiers in Materials, 2022)
Zirconia has occupied an increasingly important role in oral clinical applications in recent years. However, how to achieve the ideal bonding effect of zirconia is a significant problem that needs to be solved urgently in oral clinics. Hot etching treatment of zirconia is a hot spot of current research, but it is still unclear about the optimal acid solution and the effect of hot etching on the surface topography and bond strength of zirconia. This study evaluated the effect of hot etching with HF and HCl on the surface topography, roughness, crystalline phase, zirconia/resin cement interfacial evaluation and shear bond strength of zirconia. The results showed that the hot etching groups produced completely different topographical changes on the surface of zirconia than the sandblasting group. Obvious interfacial cracks were observed in the sandblasting group. The HF hot etching group achieved the highest roughness values (78.17± 4.94nm) and the highest shear bond strength (25.09±4.09MPa). Compared with HCl, hot etching with HF could achieve more uniform and dense porous morphology, greater roughness and shear bond strength. Moreover, there were no prominent zirconia/resin cement interfacial cracks and crystal phase transformations on the surface of zirconia.